A bioactive implant in situ and long-term releases combined drugs for treatment of osteoarticular tuberculosis. (September 2018) - Zhou, Chao-Xi; Li, Litao; Ma, Yi-Guang; Li, Bing-Nan; Li, Guang; Zhou, Zhihang; Shi, Feng; Weng, Jie; Zhang, Cong; Wang, Fenghua; Cui, Xu; Wang, Lei; et al.
Abstract: Anti-tuberculosis chemotherapy with a long duration and adequate dosing is the mainstay for treatment of osteoarticular tuberculosis (TB). However, it is difficult for systemic administration to reach adequate local drug concentrations and achieve effective treatment. Herein, a hydroxyapatite (HA) scaffold implant combined with a drug-releasing system was designed to achieve in situ and long-term anti-TB drug release and highly efficient therapeutic activity in vitro and in vivo . The clinical anti-TB drugs hydrophilic isoniazid (INH) and hydrophobic rifampicin (RFP) were molecularly dispersed into polyvinyl alcohol (PVA) through immersion-curing techniques and were steadily adhered onto the surfaces of HA scaffolds (HA-drug@PVA). The HA-drug@PVA scaffolds showed a long-term, sustained drug release profile and killed proliferating Mycobacterium in vitro . In vivo experimental results revealed that the HA-drug@PVA scaffolds provided over 10- and 100-fold higher concentrations in muscles and bones, respectively, as well as a much lower concentration (<0.025) in blood. Furthermore, the HA-drug@PVA scaffold implanted in an osteoarticular TB rabbit model showed obvious bone regeneration and fusion due to the inhibition of TB-associated inflammatory changes. The excellent therapeutic effects indicate that in situ implant materials combined with a long-term drug release system are promising for the treatment of osteoarticular TB and other osteoarticular infections.